Sirolimus and Primary Prevention of Non-melanoma Skin Cancer in Kidney Transplant Recipients – A Retrospective Study - Pinho, André (2016)
Introduction: Immunosuppression plays a central role in the pathogenesis of skin cancer in kidney transplant recipients. Recently, the potential for sirolimus to reduce the incidence of non-melanoma skin cancer in this population has been studied.Objective: To analyse the relationship between initial maintenance immunosuppressive regimens and the onset of non-melanoma skin cancer – squamous cell carcinoma and basal cell carcinoma – in kidney transplant recipients.Methods: Retrospective analysis of clinical records belonging to patients submitted to kidney transplantation between years 2002 and 2012, which were subsequently evaluated for the first time, in our Dermatology Department. Kidney transplant recipients were divided in three groups according to the initial maintenance immunosuppressive regimen: group A (sirolimus-based), group B (tacrolimus-based) and group C (cyclosporine-based).Results: Of the 188 patients studied 24.5% (n=46) were diagnosed with 83 non-melanoma skin cancer (42 basal cell carcinoma and 41 squamous cell carcinoma). There were no differences in survival free of non-melanoma skin cancer and basal cell carcinoma, between groups. The survival free of first squamous cell carcinoma was significantly higher in the group A (mean 10.7 years) than in groups B (mean 7.48 years) and C (mean 8.29 years). Crude hazard ratio of squamous cell carcinoma was 7.74 in group C (p=0.05) and 9.02 in group B (p=0.03), comparing with group A. However, after adjustment for age at date of transplantation these values lost statistical significance.Conclusion: Although the switch to sirolimus has been proven to be beneficial in secondary prevention of squamous cell carcinoma in kidney transplant recipients, its use ab initio does not seem to have the same protective effect.